SKRINING FITOKIMIA DARI EKSTRAK DAUN KANGKUNG PAGAR (Ipomoea carnea Jacq) DAN UJI ANTIBAKTERI TERHADAP Bacillus subtilis - Ermi Abriyani; Lia Fikayuniar; Iin Lidia Putama Mursal; Dedeh Komalasari (Jurnal Buana Farma, 2024)
Kangkung Pagar (Ipomoea carnea Jacq) leaves is one of the plants that is used as a treatment. This study aims to determine the content of secondary metabolites and antibacterial activity of kangkong pagar leaves against Bacillus subtilis. Extraction using maceration method with n-hexane, ethyl acetat and methanol. Antibacterial assay using well diffusion method. The extract concentrations used were 40%, 60%, 80% and 100%. The positive control used was Ciprofloxacin and the negative control used was DMSO 5%. Data were analyzed by one way ANOVA test followed by Post Hoc Tukey test. The results showed that the extracts of ethyl acetate, methanol and n-hexane had a minimum inhibitory concentration of 40% with inhibition zones formed of 8.23 ​​mm, 9.4 mm and 4.2 mm. Meanwhile, at the highest concentration of 100%, an inhibition zone of 12.6 mm was formed in the ethyl acetate extract, 15.23 mm in the methanol extract and 11.4 mm in the n-hexane extract. The results showed that extract of Kangkung Pagar (Ipomoea carnea Jacq)leaves was able to inhibit the growth of Bacillus subtilis bacteria.